Work psychology : understanding human behaviour in the workplace - Arnold, John (Harlow : Prentice Hall, 2005)
The aim of this established text is to examine the contribution of psychological theory to our understanding of human behavior at work. Its accessible and user-friendly style makes it suitable for readers unfamiliar to the theory of work psychology as well as for those with a basic grounding in the subject.
The text covers both personnel issues such as selection and training and organizational issues such as decision making, thus making it a comprehensive study of human behavior in the workplace. Throughout the text, real-life examples and illustrations are used to support the theory, to show how the concepts dealt with actually apply to work settings.
Chapter 15 Understanding organizational change and culture
Keywords: industrijska psihologija